Economic Freedom and Religion: An Empirical Investigation - Arye L. Hillman; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2016)
There has been much study of the consequences of economic freedom but, outside of the role of political institutions, there has been little study of the determinants of economic freedom. We investigate whether religion affects economic freedom. Our cross-sectional dataset includes 137 countries averaged over the period 2001-2010. Simple correlations show that Protestantism is associated with economic freedom, Islam is not, with Catholicism in between. The Protestant ethic requires economic freedom. Our empirical estimates, which include religiosity, political institutions, and other explanatory variables, confirm that Protestantism is most conducive to economic freedom.
Keywords: D63; I39; J16; O11; Z12; 330; economic freedom; protestant ethic; religion; religiosity; Catholicism; Islam; democracy; autocracy